Identifying the Promoters of Students’ Sustainable Behaviour: An Empirical Study - Dan Dacian Cuzdriorean; Szilveszter Fekete; Alina Beattrice Vladu (Amfiteatru Economic)
The present empirical study assessed factors as environment, education, social pressure and government actions from the perspective of promoters of sustainable behavior of students. In this regard a survey was conducted in one of the largest university in Romania. Our results documented as having a significant impact only factors as education and environment. Our study aims to provide a benchmark in measuring future efforts made by universities in their quest to become sustainable. By examining students' views on sustainable development, the present study covers a quasi-non-existent segment in the academic literature. The importance of our study is grounded mainly on the assumptions on the Theory of planned behavior (Ajzen, 1991), which links the individuals’ attitudes with their behavior. Implications of our results are also discussed.